Modulation of the Structure and Properties of Uranyl Ion Coordination Polymers Derived from 1,3,5-Benzenetriacetate by Incorporation of Ag(I) or Pb(II) - Thuéry, Pierre; Harrowfield, Jack (Inorganic chemistry, 2016)
Reaction of uranyl nitrate with 1,3,5-benzenetriacetic acid (H3BTA) in the presence of additional species, either organic bases or their conjugate acids or metal cations, has provided 12 new crystalline complexes, all but one obtained under solvo-hydrothermal conditions. The complexes [C(NH2)3][UO2(BTA)]·H2O (1) and [H2NMe2][UO2(BTA)] (2) crystallize as one- or two-dimensional (1D or 2D) assemblies, respectively, both with uranyl tris-chelation by carboxylate groups and hydrogen-bonded counterions but different ligand conformations. One of the bound carboxylate units is replaced by chelating 1,10-phenanthroline (phen) or 3,4,7,8-tetramethyl-1,10-phenanthroline (Me4phen) in the complexes [(UO2)3(BTA)2(phen)3]·4H2O (3) and [(UO2)3(BTA)2(Me4phen)3]·NMP·3H2O (4) (NMP = N-methyl-2-pyrrolidone), which are a 2D network with honeycomb topology and a 1D polymer, respectively. With silver(I) cations, [UO2Ag(BTA)] (5), a three-dimensional (3D) framework in which the ligand assumes various chelating/bridging coordination modes, and the aromatic ring is involved in Ag(I) bonding, is obtained. A series of seven heterometallic complexes results when lead(II) cations and N-chelating molecules are both present. The complexes [UO2Pb(BTA)(NO3)(bipy)] (6) and [UO2Pb2(BTA)2(bipy)2]·3H2O (7), where bipy is 2,2′-bipyridine, crystallize from the one solution, as 1D and 2D assemblies, respectively. The two 1D coordination polymers [UO2Pb(BTA)(HCOO)(phen)] (8 and 9), again obtained from the one synthesis, provide an example of coordination isomerism, with the formate anion bound either to lead(II) or to uranyl cations. Another 2D architecture is found in [(UO2)2Pb2(BTA)2(HBTA)(H2O)2(phen)2]·2H2O (10), which provides a possible example of a Pb–oxo(uranyl) “cation–cation” interaction. While [UO2Pb(BTA)(HCOO)0.5(NO3)0.5(Me2phen)] (11), where Me2phen is 5,6-dimethyl-1,10-phenanthroline, is a 1D assembly close to those in 6 and 8, [UO2Pb2(BTA)2(Me4phen)2] (12), obtained together with complex 4, crystallizes as a 2D network as a result of the high degree of connectivity provided by the chelating/bridging tricarboxylate ligand. Emission spectra measured in the solid state display vibronic fine structure attributable to uranyl luminescence (except for complex 5, in which emission is quenched), with variations in maxima positions associated with modifications of the uranyl ion environment.